UJI FITOKIMIA DAN AKTIVITAS ANTIBAKTERI EKSTRAK METANOL AKAR MERUNG (Coptosapelta tomentosa) - Dewi, Dynda Rosiana; Marliana, Eva; Pratiwi, Djihan Ryn (JURNAL ATOMIK, 2019)
Phytochemical tests and antibacterial activity of the roots of Merung plants (Coptosapelta tomentosa) have been done. This research aims to find out the content of secondary metabolites contained in the sample using the Thin Layer Chromatography method and to determine antibacterial activity by paper disc method from methanol extract Merung root (Coptosapelta tomemtosa). Based on results of phytochemical screening, it was known that methanol extract contained alkaloid, polyphenol, flavonoid and terpenoid/steroid. Methanol extract antibacterial activity against Propionibacterium acnes KCCM 11898 range of MIC of 0-1%. Methanol extract showed antibacterial activity against Escherichia coli bacteria ATCC 25922 range of MIC of 0-1%. From the results of the antibacterial activity test it can be concluded that the methanol extract have antibacterial activity against Propionibacterium acne KCCM 11898 and Escherichia coli ATCC 25922.